IMPROVING READING ENGLISH BY USING RCRR (READ, COVER, REMEMBER, RETELL) STRATEGY (CLASSROOM ACTION RESEARCH ON 8TH-GRADE STUDENTS AT SMP NEGERI 4 TONDANO) - Ali, Warini La; Pelenkahu, Noldy; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study is to find the effect of using the RCRR strategy to improve students reading comprehension at SMP Negeri 4 Tondano. This study used quantitative research with a classroom action research design. The subjects of this study were 30 students of class 8B at SMP Negeri 4 Tondano. Data were collected through pre-tests and post-tests with different questions. The data analysis results showed a difference between the pre-test total score of 1.500 and the post-test total score of 2.010. This study calculated the effect of using the RCRR strategy in class 8B using a t-test on SPSS software version 25. The results showed an effect of using the RCRR strategy with Sig. (2-tailed) of .000 < 0.05. The alternative hypothesis (Ha) is accepted, while the null hypothesis (H0) is rejected. Therefore, using the RCRR strategy effectively improves students reading comprehension.